Pendidikan Agama Islam dalam Membangun Peradaban Berbasis Nilai Kemanusiaan - Syarifudin Zaidan, Akmal; Ulya Maysyaroh; M Shodrus Syahid Khusamudin; Ari Abi Aufa; Oseolla Savana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article discusses the role of Islamic Religious Education (PAI) in building a civilization based on humanitarian values in the midst of building a civilization based on human values in the midst of modernization and globalization. challenges of modernization and globalization. PAI functions as a pillar in shaping the character of shaping the character of individuals who are intellectually intelligent and have social and spiritual awareness. Through the cultivation of values such as honesty, justice, compassion, and tolerance, PAI contributes to creating a noble generation. in creating a noble generation. However, PAI faces challenges such as secularization of education and external cultural influences. This article proposes strengthening strategies, including the integration of science with Islamic values and improving the quality of educators. The research method used is a literature study with a qualitative descriptive approach, which involved analyzing literature related to the role of PAI. The contribution of this research lies in the in-depth understanding of the role of PAI, despite the limitations in empirical data. there are limitations in empirical data. Further research is needed to explore the concrete impact of PAI in various educational contexts.